Creating a technology-enhanced constructivist learning environment for research ability development in a BA Thesis Writing course. Issue 5 (3rd July 2020) - Gu, Peiya; Zhang, Ye; Gu, Haibo
Abstract: This qualitative case study investigates the technology-enhanced constructivist learning environment (CLE) for developing undergraduate English-majors' research abilities at a Chinese university. The faculty group attempted at transforming an English Writing course into BA Thesis Writing, supported by a free online learning management system (Moodle) with multi-faceted scenario, resources, tools and management. Situated in the broader context of the 10-year curriculum reform, two BA Thesis Writing classes from two semesters were examined using observation notes, interviews and student products. Findings show the CLE has enhanced the students' problem-based learning (PBL) processes and research ability development in terms of problem awareness, information literacy, reasoning and research designing. The CLE contributed to the whole learning experience by continuous instructional support, forum discussions, and information resources and tools. However, faculty tended to avoid teaching such a course because it is not only demanding but it clashes with norms of Chinese higher education in terms of professional values, pedagogical philosophy and institutional culture. The paper concludes by assessing the reform efforts' overall gains and challenges, and its implications for future technology integration in foreign language learning and teaching in China.